Effects of force detecting sense organs on muscle synergies are correlated with their response properties. Issue 4 (July 2017) - Zill, Sasha N.; Neff, David; Chaudhry, Sumaiya; Exter, Annelie; Schmitz, Josef; Büschges, Ansgar
Abstract: Sense organs that monitor forces in legs can contribute to activation of muscles as synergist groups. Previous studies in cockroaches and stick insects showed that campaniform sensilla, receptors that encode forces via exoskeletal strains, enhance muscle synergies in substrate grip. However synergist activation was mediated by different groups of receptors in cockroaches (trochanteral sensilla) and stick insects (femoral sensilla). The factors underlying the differential effects are unclear as the responses of femoral campaniform sensilla have not previously been characterized. The present study characterized the structure and response properties (via extracellular recording) of the femoral sensilla in both insects. The cockroach trochantero-femoral (TrF) joint is mobile and the joint membrane acts as an elastic antagonist to the reductor muscle. Cockroach femoral campaniform sensilla show weak discharges to forces in the coxo-trochanteral (CTr) joint plane (in which forces are generated by coxal muscles) but instead encode forces directed posteriorly (TrF joint plane). In stick insects, the TrF joint is fused and femoral campaniform sensilla discharge both to forces directed posteriorly and forces in the CTr joint plane. These findings support the idea that receptors that enhance synergies encode forces in the plane of action of leg muscles used in support and propulsion. Highlights: Sensory receptors that monitor forces can reinforce muscle synergies. We tested whether receptor response properties determine effects on synergies. Depressor muscles provide support/propulsion in stick insects and cockroaches. Femoral campaniform sensilla show species-specific sensitivity to depressor forces. Effects on muscle synergies are correlated with sensory response properties.